Tantangan Pasca Operasi Implan Koklea: Pengalaman 15 Tahun di Rumah Sakit Umum Pusat Nasional Cipto Mangunkusumo - Zizlavsky, Semiramis; Priyono, Harim (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Hearing loss is a significant but often overlooked disability, particularly in developing countries as Indonesia, where access to specialized care is still limited. Purpose: To review the 15-years experience of cochlear implantation services at Cipto Mangunkusumo National General Hospital. Method: A retrospective study of children aged 0–18 years with profound hearing loss who underwent cochlear implant surgery between 2009 and 2023. Data were collected from medical records, including patient demographics, surgical outcomes, and complications. Result: A total of 255 patients (318 ears) received cochlear implants, with the majority aged 3–5 years (37.6%), and 54.5% male. Unilateral implants were predominant (75.3%). In 2020, a 92% decline in surgeries was noted due to the COVID-19 pandemic, which led to the postponement of elective and non-urgent cases. Post-surgical complications occurred in 4.3% of patients, with facial nerve stimulation being the most common side effects (36.4%). Conclusion: Despite expanding services, there still some obstacles remained, including high costs, limited access to specialized care, and unequal distribution of skilled professionals. Addressing these challenges is crucial to improving patient outcomes, and ensuring the sustainability of cochlear implant programs in Indonesia.